Constraint Dynamics in Rainfed Pulse Farming: A Case of the Seed Hub Project in India: RESEARCH PAPER - Anisha; Meena, Mohar Singh; Mahendra Kumar; Banwari Lal; S.K.Meena (Annals of Arid Zone, 2025)
As the world’s largest producer and consumer of pulses, India faces a persistent paradox: despite its central global role, national pulse productivity remains hindered by a range of biophysical, socio-economic, and institutional challenges. This study highlights the significant constraints limiting pulse productivity, drawing insights from farmers in the Nagaur district of Rajasthan, where a pulse seed hub has been established by the Ministry of Agriculture and Farmers Welfare at KVK, Nagaur, under the administrative control of Agriculture University, Jodhpur. The findings reveal that abiotic challenges are the most severe, with farmers reporting acute limitations due to lack of irrigation, extreme temperatures, and terminal drought. Resource-related constraints such as labor scarcity and inadequate access to credit further aggravate production difficulties. Marketing issues, including high transportation costs and the prevalence of unregulated markets, also restrict farmers’ ability to benefit from pulse cultivation. The study indicates that farmers with higher education, higher income, larger landholdings, and stronger social participation tend to perceive fewer constraints. This demonstrates the crucial role of socio-economic empowerment in managing production challenges. Given these realities, there is an urgent need for targeted interventions that focus on improving irrigation infrastructure, enhancing credit accessibility, developing resilient pulse varieties, and strengthening market linkages, particularly for small and marginal farmers. Strengthening farmers’ organisations and institutional support systems is imperative for enhancing pulse productivity and enabling India to fully realize its potential as the global leader in pulse production.